2022
DOI: 10.1155/2022/2343679
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and Genetic Characterization of Toxoplasma gondii among Children with Neurodevelopmental Disorders in Egypt

Abstract: Toxoplasma gondii is a parasite with a special predilection for the central nervous system. Toxoplasmosis's contribution to the triggering of many neurodevelopmental disorders was established. This study aimed to detect the seroprevalence and genotypes of T. gondii strains in children with neurodevelopmental disorders. The study included 180 children with neurodevelopmental disorders and 180 children in the control group. Assessment of seropositivity of Toxoplasma IgM and IgG antibodies in patients and control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Similarly, our subgroup meta-analysis of cross-sectional studies based on the type of mental disorder indicated that, patients with neurodevelopmental disorder followed by patients with bipolar and related disorders had the highest prevalence rate of toxoplasmosis. Previous studies showed that the seropositivity rates of anti- Toxoplasma antibodies were significantly higher in patients with neurodevelopmental disorders than in controls [ 29 32 ]. Furthermore, a meta-analysis study on 4021 patients diagnosed with bipolar disorder and 8669 healthy controls indicated that this disorder was associated with 1.34-fold higher risk of seropositivity for toxoplasmosis than healthy individuals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, our subgroup meta-analysis of cross-sectional studies based on the type of mental disorder indicated that, patients with neurodevelopmental disorder followed by patients with bipolar and related disorders had the highest prevalence rate of toxoplasmosis. Previous studies showed that the seropositivity rates of anti- Toxoplasma antibodies were significantly higher in patients with neurodevelopmental disorders than in controls [ 29 32 ]. Furthermore, a meta-analysis study on 4021 patients diagnosed with bipolar disorder and 8669 healthy controls indicated that this disorder was associated with 1.34-fold higher risk of seropositivity for toxoplasmosis than healthy individuals [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Non-archetypal strains have also been identified in cases of congenital toxoplasmosis, and were associated with severe infection [ 102 ]. In Egypt, T. gondii seropositivity was found to be significantly higher in children with hydrocephalus and epilepsy; the presence of non-archetypal strains was confirmed by PCR–RFLP [ 103 ]. The strain should also be taken into consideration as a potentially important factor in the case of pregnant women, as it may have an impact on fetus survival, as well as on the severity of a newborn’s ocular and/or cerebral impairment [ 104 ].…”
Section: Toxoplasma Gondii Non-archetypal Strains: Virulence...mentioning
confidence: 99%